Entrepreneurial Orientation towards Business Performance: A Study on Tunas Mekar Participants / Azlin Shafinaz Arshad ... [et al.] - Arshad, Azlin Shafinaz; Mohd Zain, Zahariah; Abd Rashid, Arlinah; Arshad, Afiza Azura; Ariffin, Azita Dolly; Mokhtar, Marziah; Zahari, Ainaa Salihah
Tunas Mekar Programme, a smart partnership arrangement between Bumiputera graduates and SME entrepreneurs using the mentor-mentee concept, was launched back in 2005. This programme involves SMEs entrepreneur (mentor) sharing their experiences as an entrepreneur and the graduates (mentee) who will then share the knowledge and expertise they had acquired during their studies. This study aims to determine entrepreneurial orientation of Tunas Mekar participants and identify the most significant dimensions that affect business performance. Entrepreneurial orientation comprises methods, processes, practices, styles and decision-making activities engaged by entrepreneurs that lead into new marketplaces. For this study, simple random sampling method was adopted and 150 questionnaires were distributed to Tunas Mekar participants where only 104 were deemed usable. The study discloses Tunas Mekar participants possess entrepreneurial orientation characteristics; innovative, proactive as well as being risk-takers. Innovativeness was found to have the most significant impact towards their business performance compared to proactiveness and risk-taking. This study provides some understanding and information on Bumiputera entrepreneurs' in terms of their entrepreneurial orientations.